2007
DOI: 10.1149/1.2430691
|View full text |Cite
|
Sign up to set email alerts
|

Improved Wetting of Mixed Ionic/Electronic Conductors Used in Electrochemical Devices with Ternary Air Braze Filler Metals

Abstract: This paper reports on the wetting behavior, reactivity, and long-term electrical conductance of a series of ternary filler metals being considered for brazing lanthanum strontium cobalt ferrite ͑LSCF͒-based oxygen separation membranes. Mixed ionic/electronic conducting perovskite oxides such as LSCF and various doped barium cerates are currently being considered for use in hightemperature electrochemical devices such as oxygen and hydrogen concentrators and solid oxide fuel cells. However, to take full advanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 13 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…In a subsequent study by the same research group, the addition of TiO 2 was found to be beneficial in reducing the contact angle on LSCF-6428, just as with alumina as a substrate. 243 However, the addition of TiO 2 enables SrTiO 3 to be formed as an interfacial reaction product, the extent of which needs to be carefully controlled to produce mechanically robust joints with suitable levels of electrical resistivity. Another potential application for RAB is in the joining and sealing of planar SOFCs.…”
Section: Ag-based Reactive Air Brazingmentioning
confidence: 99%
“…In a subsequent study by the same research group, the addition of TiO 2 was found to be beneficial in reducing the contact angle on LSCF-6428, just as with alumina as a substrate. 243 However, the addition of TiO 2 enables SrTiO 3 to be formed as an interfacial reaction product, the extent of which needs to be carefully controlled to produce mechanically robust joints with suitable levels of electrical resistivity. Another potential application for RAB is in the joining and sealing of planar SOFCs.…”
Section: Ag-based Reactive Air Brazingmentioning
confidence: 99%
“…Reactive brazing in air has been shown to be suitable for joining BSCF to high-temperature-resistant metals [ 25 , 26 , 27 , 28 ]. In addition, other OTM materials such as LSCF [ 29 , 30 ], BCFN [ 31 ], or dual-phase membranes [ 32 , 33 , 34 ] were joined using reactive air brazing. Suitable metallic joining partners show a similar thermal expansion to the ceramic OTM.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, reactive elements that oxidize during brazing in air have been added to promote silver wetting on various ceramic substrates including zirconia, 11,12 lanthanum strontium cobalt ferrite (LSCF), 13,14 and gadolinium-doped ceria (GDC). 15 Critically, the oxides in these Reactive Air Brazes (RABs) (most commonly CuO, 8 V 2 O 5, 16 etc.…”
mentioning
confidence: 99%